Application of a chemiluminescence immunoassay system and GC/MS for toxicological investigations on skeletonized human remains. (July 2019) - Basilicata, P.; Pieri, M.; Simonelli, A.; Faillace, D.; Niola, M.; Graziano, V.
Graphical abstract: Highlights: Hair, larvae and cardiac tissue from a skeletonized body were analyzed. A chemiluminescence-based immunoassay system was used for drugs screening. All specimens results positive to COC and MOR, larvae and hair also to BDZ. Apart BDZ in larvae, all results were confirmed by GC/MS. Death was attributed to overdose by COC and MOR in a poly-addicted subject. Abstract: Hair, larvae and cardiac muscle, the only biological samples present on a skeletonized human body found in a rural area, were used for forensic toxicological analyses in order to determine possible causes of death. Since no information about the victim or the circumstances of death was available (except for the place where the corpse was found, known to be a gathering place for drug addicts), the first approach for the analysis of non-conventional matrices involved the screening of different classes of active principles, using a chemiluminescence-based screening assay designed for whole blood. The immunoassay test results showed positivity to amphetamines, cocaine and opiates on water/methanol extract from cardiac tissue, larvae and hair samples. Gas chromatography–mass spectrometry (GC/MS) analyses confirmed the immunoassay results, except for amphetamines. The minimal sample preparation (hydration and extraction in an ultrasonic bath), the reduced sample volume required for the analyses, together with the correctness of results as confirmed by GC/MS, showed the suitability of the screening test for forensic applications on non-conventional matrices. Quantitative analyses in GC/MS allowed the cause of death to be ascertained on the basis of the ratio between parent drugs and metabolites.